In Memoriam: Prof. Volodymyr Oleksandrovych Naumenko (Ukrainian Journal of Ophthalmology, 2025)
Volodymyr Oleksandrovych Naumenko, Deputy Head for Medical Research at the Filatov institute, Professor, Dr Sc (Med), and a recipient of the State Prize of Ukraine, suddenly passed away on 1 December 2022 at the age of 53. The staff of the institute, and his friends and colleagues over Ukraine, mourn his death.